Work Value Congruence and Satisfaction at Work: Is this Western Concept Applicable to a Developing Country such as Malaysia? - Ahmad, K.Z. (Faculty of Business and Accountancy, University of Malaya, 2008)
This study aims to fulfil two literature gaps in the person-environment fit theory, in particular the supply-value fit or S-V fit relating to work congruence. Firstly, previous research in S-V fit tended to look mainly at autonomy and supervision style. However, there appears to be no reported research that has simultaneously investigated, in a single study, the effects of the discrepancy between the perceived and desired levels of work quantity, variety, power, responsibility and concentration required for the job and its relationship with satisfaction at work. Secondly, the S-V fit theory has been relatively established in developed countries such as America and Britain. However, it would be interesting to discover whether the theory is also applicable among workers in small isolated towns in a developing country such as Malaysia. Questionnaires were distributed and collected from two hundred and eighty respondents working in small towns in Peninsular Malaysia. Support for the S-V fit theory was obtained, as results suggested that the greater the discrepancy between the supplies and values of work quantity, variety, power, responsibility and concentration required at work, the lesser was the satisfaction.